Persepsi Karakter Siswa Terhadap Dampak Tiktok di SDN 04 Kubang Putiah - Elyza Furwati; Marefni M; Puti Andam Dewi (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The aim of this research is to find out how SDN 04 Kubang Putiah students' perceptions of using the Tik Tok application are influenced by internal and external factors in forming a perception. The research carried out was qualitative research. Penetta informants used purposive sampling and stratified sampling techniques with several informants. With the results of research on the perceptions of students at SDN 04 Kubang Putiah in using the Tik Tok application, there are many perceptions in a negative direction and only a few of the students have positive perceptions from using the TikTok application. which is formed based on the benefits provided and negative perceptions where Tik Tok does not provide benefits for users. From positive and negative perceptions, there are many factors that influence perceptions, namely internally and externally from the individual user.